Class II malocclusion therapy using fixed orthodontic appliance - Škufca Bojan; Jelenić Tatjana (Vojnosanitetski Pregled, 2007)
Background. Depending on the indication, and the age of a patient, class II division I malocclusion can be treated by a fixed or mobile orthodontic appliance, with or without teeth extraction. Case report. A treatment of a male patient, 15 years old, with dentoalveolar class II division I was described. On the base of clinical findings, study case analysis, analysis of orthopan and profile cephalogram, there were class II division I with protrusion of frontal teeth and mild crowding in lower jaw assessed. The patient was treated by fixed orthodontics appliances (SWA Roth .022") in both jaws for 18 months, with the retention period of the same length. Conclusion. Fixed ortodontic appliances are necessary when bodily movement of the teeth is indicated - in this case for cuspids distalization and retraction of incisors.